2018
DOI: 10.1111/cogs.12616
|View full text |Cite
|
Sign up to set email alerts
|

Are Words Easier to Learn From Infant‐ Than Adult‐Directed Speech? A Quantitative Corpus‐Based Investigation

Abstract: We investigate whether infant-directed speech (IDS) could facilitate word form learning when compared to adult-directed speech (ADS). To study this, we examine the distribution of word forms at two levels, acoustic and phonological, using a large database of spontaneous speech in Japanese. At the acoustic level we show that, as has been documented before for phonemes, the realizations of words are more variable and less discriminable in IDS than in ADS. At the phonological level, we find an effect in the oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 83 publications
(164 reference statements)
5
11
0
Order By: Relevance
“…To conclude, we found that advantages in segmentability for CDS over ADS in an ecological corpus were smaller and more inconsistent than previous estimations based on laboratory CDS–ADS. Overall, our word segmentation results align with other work on sound discriminability (Martin et al, 2015) and word discriminability (Guevara-Rukoz et al, 2018), suggesting that the high learnability attributed to CDS may have been overestimated. Research assessing the learnability properties of child-directed speech at other levels (e.g., syntax) would benefit from using similarly natural corpora, as well as a variety of algorithmic approaches.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To conclude, we found that advantages in segmentability for CDS over ADS in an ecological corpus were smaller and more inconsistent than previous estimations based on laboratory CDS–ADS. Overall, our word segmentation results align with other work on sound discriminability (Martin et al, 2015) and word discriminability (Guevara-Rukoz et al, 2018), suggesting that the high learnability attributed to CDS may have been overestimated. Research assessing the learnability properties of child-directed speech at other levels (e.g., syntax) would benefit from using similarly natural corpora, as well as a variety of algorithmic approaches.…”
Section: Discussionsupporting
confidence: 88%
“…Although children are exposed to both child-directed speech (CDS) and adult-directed speech (ADS), children appear to extract more information from the former than the latter (e.g., Cristia, 2013; Shneidman & Goldin-Meadow, 2012). This has led some to propose that most or all linguistic phenomena are more easily learned from CDS than ADS (e.g., Fernald, 2000), with a flurry of empirical literature examining specific phenomena (see Guevara-Rukoz et al, 2018, for a recent review). Deciding whether the learnability of linguistic units is higher in CDS than ADS is difficult for at least two reasons: It is difficult to find appropriate CDS and ADS corpora; and one must have an idea of how children learn to check whether such a strategy is more successful in one register than the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While at segmental level no advantage of IDS was observed, when looking at other linguistic levels, for instance prosodic boundary detection [24] or lexical segmentation [25], IDS does have an advantage. Nevertheless, when combining both acoustic and lexical information for word form learning, an overall detrimental effect for IDS was obtained [26].…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is generally adaptive because stored word sound memories and related perceptual mechanisms must be flexible enough to support cross‐contextual comprehension on the fly, for instance when a learner encounters a known word in an unfamiliar dialect (Church & Fisher, ). Furthermore, the number of minimally different words that young children know and hear regularly in the speech directed to them is limited (Guevara‐Rukoz et al, ), and this makes it reasonable to classify a novel sound sequence that is very similar to a known word as an instance of that known word instead of as an instance of an unknown word (Swingley & Aslin, ).…”
Section: Introductionmentioning
confidence: 99%